Extraovarian granulosa cell tumor: A case report - El Marouni, Abdelouhab; Aziz, Karam; Toghrai, İmane and Mazaz, Khalid and Ibn Majdoub, Karim (Journal of Surgery and Medicine, 2019)
Granulosa cell tumor (GCT) of the ovary is a rare tumor representing 2 to 5% of all ovarian neoplasms. It can reproduce or metastasize several years after the initial treatment. In rare cases, CGT can develop on an extra-ovarian site, which is thought to originate from ectopic gonadal tissue along the embryonic genital ridge. We herein present a case of extraovarian granulosa tumor, the clinical and therapeutic aspects, and our approach.